The Effect of Geometry Parameters and Flow Characteristics on Erosion and Sedimentation in Channel’s Junction using Finite Volume Method - Mohammadamin Torabi; Amirmasoud Hamedi; Ebrahim Alamatian; Hamidreza Zahabi (International Journal of Engineering and Management Research, 2019)
One of the most critical problems in the river engineering field is scouring, sedimentation and morphology of a river bed. In this paper, a finite volume method FORTRAN code is provided and used. The code is able to model the sedimentation. The flow and sediment were modeled at the interception of the two channels. It is applied an experimental model to evaluate the results. Regarding the numerical model, the effects of geometry parameters such as proportion of secondary channel to main channel width and intersection angle and also hydraulic conditionals like secondary to main channel discharge ratio and inlet flow Froude number were studied on bed topographical and flow pattern. The numerical results show that the maximum height of bed increased to 32 percent as the discharge ratio reaches to 51 percent, on average. It is observed that the maximum height of sedimentation decreases by declining in main channel to secondary channel Froude number ratio. On the assessment of the channel width, velocity and final bed height variations have changed by given trend, in all the ratios. Also, increasing in the intersection angle accompanied by decreasing in flow velocity variations along the channel. The pattern of velocity and topographical bed variations are also constant in any studied angles.